2018
DOI: 10.1093/jisesa/iey013
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Abridged Life Tables for Cephalonomia stephanoderis and Prorops nasuta (Hymenoptera: Bethylidae) Parasitoids of Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae) Reared on Artificial Diet

Abstract: Biological aspects and demographic parameters of Cephalonomia stephanoderis Betrem (Hymenoptera: Bethylidae) and Prorops nasuta Waterston (Hymenoptera: Bethylidae) parasitoids of the coffee berry borer (CBB), Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae) were investigated using diet-reared CBB hosts. Developmental time from eggs to adults, oviposition, and postoviposition period were comparable for both parasitoids. However, P. nasuta had a considerably longer preoviposition and longevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The intrinsic growth rate ( r ) of 0.067 indicated that the reproduction rate of P. coffea is similar to that of H. hampei (0.067) (Portilla and Streett 2008), much lower than that of C. stephanoderis (0.089), but higher than P. nasuta (0.052) (Portilla et al 2014 and Portilla and Grodowitz 2018). However, unlike those ectoparasitoids, P. coffea does not need to consume immatures of CBB to achieve its reproductive potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic growth rate ( r ) of 0.067 indicated that the reproduction rate of P. coffea is similar to that of H. hampei (0.067) (Portilla and Streett 2008), much lower than that of C. stephanoderis (0.089), but higher than P. nasuta (0.052) (Portilla et al 2014 and Portilla and Grodowitz 2018). However, unlike those ectoparasitoids, P. coffea does not need to consume immatures of CBB to achieve its reproductive potential.…”
Section: Discussionmentioning
confidence: 99%
“…Life fertility tables were calculated according to Portilla et al (2014) and Portilla and Grodowitz (2018). Portilla et al (2014) explained step by step the calculations of three species of insects and their abridged cohort life table constructions based on formulae and definitions from Carey (1993) and Krebs (2001).…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to know the CBB behavior under field conditions, as well as its interactions with climatic factors. Thus, an efficient IPM program integrating several control measures may be implemented (Portilla;Grodowitz, 2018). The previous evaluation carried out immediately before the first spraying of the insecticides revealed that the infestation level found (2.5% -3.5%) was in agreement or slightly higher than the recommended (1.0% -3.0%) to start controlling CBB (Matiello et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For the management of coffee borer, it is necessary to know the bio-ecology of the insect and its interaction with the environment to determine its management, integrating several forms of control (MICHAEL;PORTILLAR, 2018). The application of insecticides is the most widely used method of control and is responsible for the 1940 revolution in insect control, as it has been the most efficient and economical means of combating insects, especially if the objective is to maximize crop productivity in large areas (SOUSA, 2013).…”
Section: Introductionmentioning
confidence: 99%